Cyclic frame discarding multiplexer design - Shah, Asadullah; Dwi Handayani, Dini Oktarina (IIUM Press, 2011)
The cyclic frame discarding is an approach in which at least for each user a packet is discarded before attempting to discard a second packet fonn the same. The idea is to avoid consecutive packet discarding from a single user when there is higher load. To do so, a slightly better perfonnance, in tenns of speech quality is achieved than a random packet dropping that suffers from consecutive packet losses. This chapter explains the benefit that can be achieved by controlling the packet discarding mechanism in a cyclic way.